Synthesis and Characterization of Lanthanide(III) Complexes with 2[(2,6-dichlorophenyl) amino] benzene acetic acid - Lokhande, M.V.; Deshpande, M.N. (Asian Journal of Chemistry, 2010)
Lanthanide(III) complexes with 2[(2,6-dichlorophenyl) amino] benzene acetic acid (DPABA) with the general composition [Ln(DPABA)3·2H2O] were prepared and characterized by IR, NMR, TGA, DTA, elemental analysis, X-ray diffraction, molar conductance and magnetic moment. The spectral studies suggest that ligand behaves as bidentate. The study indicates that the coordination number is eight of the central metal ion. There is slight participation of 4f electron in bonding.